THE EXPANDING MODEL OF THE CONFORMALLY FLAT NON-STATIC SPHERICALLY SYMMETRIC PERFECT FLUID DISTRIBUTIONS - Borkar, Dr. Manjusha Hajare (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The explicit expressions for pressure, density expansion, rotation, sheer and non vanishing component of flow vector have been obtained. In this this note ,we have discussed the various geometrical and physical properties of spherically symmetric metric space time obtained by Roy and Bali [5] by considering the triples of orthogonal unit vectorsα_i, β_i. Here we connect all the physical quantities obtained by Roy and Bali [5] with mathematical quantities ρ^a in Borkar and Hajare [3]. Further it is noticed that the model is expanding, rotating, shearing but non geodetic.